Retraditionalisation in social economy: An example of school cooperatives - Nosal, Przemysław; Waligóra, Anna (Social Entrepreneurship Review, 2017)
The retraditionalisation is a useful tool to Polish social economy (SE) analysis. The aim of this paper is emphasizing the “traditional turn” in nowadays ES. To achieve this goal an example of the tradition and functioning of student cooperatives is used. Content analysis (quantitative and qualitative data), a survey with primary, secondary and post-gymnasium schools from the area of Poznan and individual in-depth interviews was conducted in the years 2015-2017. The most important finding of this text is pointing at the retraditionalisation as the key and important analytical phenomenon at the area of social economy.